Avaliação, caracterização e reutilização do resíduo agroindustrial vitivinícola - Trappel, Maicon Diego Ribeiro (Universidade do Vale do Rio dos Sinos, 2020)
This study aims to explore an area that has been poorly reached in the field of viticulture and demonstrating alternatives for destination of a grape residue. Composed of cellulose, hemicellulose, lignin, tannins and protein. This qualitative variation depends on the variety and a half where it is grown. Being the stalk lignocellulosic material with high levels of phenolic compounds, there is great potential for reusing stalk in the fabricate the MDF (Medium Density Fiberboard) and agglomerates industry. The municipality of Bento Gonçalves - RS is the main pole for grape processing and also the main furniture pole in the country, producing 62.8 million MDF pieces, which is equivalent to 74.8% of its total production. The increase in waste generation is proportional to market demand, Rio Grande do Sul increased its wine production by more than 40% in the last 16 (sixteen) years. The state that is a national highlight in the processing of grapes for the production of wine, juice and derivatives, processed 750 million kilograms of grapes in 2017, generating seasonal waste that are equivalent to 150.6 million kilograms per year, where 52.71 million kilos were composed by the stalk. In current days this waste has as its main destination the landfill or composting. The present study visa to evaluate and quantify the chemical composition of the stalk of the most processed varieties in Bento Gonçalves, Rio Grande do Sul, in order to find its valorization in the application in MDF and agglomerates. The characterization of the chemical structure of biomass be able to indicative of a potential application in the furniture industry, in comparison with the structure of other plants, the cotton that produces fibers, its secondary walls are constituted almost exclusively by cellulose, Pine trees are characteristic for producing compression wood that is enriched in lignin. In the laboratory chemical analyzes it was necessary to carry out the adaptation of the methodology, which was satisfactory for the application of biomass. Analyzed the biomass extracts in order to remove fatty acids, fatty alcohols, phenols, terpenes, steroids, resinous acids, rosins, waxes and other compounds wax, oil, phenolics soluble in organic. The varieties Isabel and Niágara, presented 52.27% and 44.54%, respectively, the Bordô variety with 23.78% of extractives, under these circumstances presenting lower levels of extractive compounds. The three grape varieties presented from 17.23% to 19.32% of legnina for the three varieties, and the amount of holocellulose for the varieties Isabel and Niágara of 27.16% and 35.54% respectively, and its test may be viable. in 9 application for use in the MDF and chipboard industry. The Bordô variety showed a greater amount of material 57.93 ± 0.66% in holocellulose content, indicating its potential for testing cellulose derivatives.
Keywords: Engaço; Uva; Bento Gonçalves; Stalk; Grape; MDF; ACCNPQ::Engenharias::Engenharia Civil